Τhe Effects of a Pilot Exercise Program of Basketball Basic Skills on Individuals with Moderate Mental Retardation - Tsikriki Γεωργία; Batsiou Σοφία; Douda Ελένη; Antoniou Παναγιώτης (Inquiries in Physical Education and Sport, 2007)
The purpose of this study was to examine if the exercise of adults with moderate mental retardation, who participated in a basketball-related practice programs, can improve their motor abilities and their physical fitness attributes. Eight students (boys=4, girls=4) with moderate mental retardation, aged 17 to 21 years participated in the study. The duration of the intervention program was 12 weeks (3 times per week, 40 minutes per training unit). The participants were divided into two groups of four members (2 girls, 2 boys) and they were exercised in the same objects. During this study two measurements (the first one at the beginning and the second at the end) were undertaken measuring: a) basketball skills through the «Basketball skills test of the Special Olympics» and b) physical fitness. Statistical analysis showed that the participants exhibited better performance during the second measurement in basketball skills and in all parameters of physical fitness. More specifically, statistically differences have been noted, in passing, in dribbling as well as in cardiovascular endurance. Having under consideration the limitations of the present study, the above results show that people with moderate mental retardation, who participate in specialized sport-specific exercise programs, can improve their physical fitness parameters. Bettering the present study higher improvement was achieved in simple basketball skills which demanded accuracy and speed or a combination of those.